The effect multiple lightning impulse on the electrical breakdown voltage insulation resistance and isolation capacitance characteristics an opto - isolator as a low voltage surge protective device [electronic resource] - Mohd. Fairuz Abdul Hamid, 1978-; Mohd. Muhridza Yaacob, supervisor (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2007